2020
DOI: 10.1155/2020/9181549
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Anticancer Effect of Dual Drug- (Cisplatin/Epigallocatechin Gallate) Loaded Gelatin Nanoparticles for Lung Cancer Treatment

Abstract: Lung cancer has the highest mortality of any cancer worldwide, and cisplatin is a first-line chemotherapeutic agent for lung cancer treatment. Unfortunately, cisplatin resistance is a common cause of therapeutic failure. The ability to overcome chemoresistance is crucial to the effective treatment of lung cancer. Recently, epigallocatechin gallate (EGCG), a type of polyphenol extracted from tea, has been shown to suppress the rapid proliferation of cancer cells, including lung cancer. We tested whether nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Moreover, merging evidence showed that several phytochemicals such as curcumin, piperine, berbamine, shikonin, genistein as well as the whole extract of some plants are able to kill CSCs (19,20). For instance, epigallocatechin-3-gallate (EGCG) as an active compound in green tea is involved in several ongoing alone or combination clinical trials with cisplatin and oxaliplatin, because of the potential to suppress cancer stemness and tumorigenicity and its ability to improve the efficacy of conventional drugs in several types of cancers including RCC (21)(22)(23). The usage of phytochemicals is likely to be a potential treatment strategy for eradicating cancer through the elimination of CSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, merging evidence showed that several phytochemicals such as curcumin, piperine, berbamine, shikonin, genistein as well as the whole extract of some plants are able to kill CSCs (19,20). For instance, epigallocatechin-3-gallate (EGCG) as an active compound in green tea is involved in several ongoing alone or combination clinical trials with cisplatin and oxaliplatin, because of the potential to suppress cancer stemness and tumorigenicity and its ability to improve the efficacy of conventional drugs in several types of cancers including RCC (21)(22)(23). The usage of phytochemicals is likely to be a potential treatment strategy for eradicating cancer through the elimination of CSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin formulations including polymeric nanoparticles, micelles, dendrimers, and liposomes have a greater chance of delivering persistent cisplatin to the growth in reaction to alterations in the tumor's microenvironment. [223][224][225][226][227] Pemetrexed is a small molecule drug that is employed in the therapy of non-squamous non-small cell lung cancer (NSCLC). It is a chemotherapeutic substance that works by inhibiting the enzymes participating in the creation of nucleotides, which are essential for DNA replication and cell division.…”
Section: -110mentioning
confidence: 99%
“…Higher cytotoxicity levels were observed in A549 cells at low drug concentrations of cisplatin at 2 μg/mL and EGCG at 5 μg/mL. At last, the researchers concluded that a combination approach of EGCG and cisplatin in NPs would be a promising anticarcinogenic candidate for treatment of lung cancer (Chen et al, 2020 ).…”
Section: Combination Based Onconanotherapeuticsmentioning
confidence: 99%